The differences of parasitemia and lungs size in malaria-associated acute respiratory distress syndrome (MA-ARDS) and non-MA-ARDS in mice infected with Plasmodium berghei ANKA - Eka Noviya Fuzianingsih; Cyuzuzo Callixte; Marselaonety La’lang; Dinda Eka Putri; Heny Arwati; Lucia Tri Suwanti (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2022)
Malaria-associated acute respiratory distress syndrome (MA-ARDS) is characterized by extensive infiltration of leukocytes, microhemorrhages, vasogenic edema, changes in lung color, and a significant increase in the weight of the lung. This study was aimed to find out the differences in parasitemia and lung size in MA-ARDSand non-MA-ARDSin mice infected with Plasmodium berghei ANKA. Sixteen male BALB/c mice were infected with P. berghei ANKA, and daily parasitemia was observed on Giemsa-stained tail blood smears. Mice were sacrificed when parasitemia reached ±20%. Simultaneously eight uninfected mice were used as negative control (NEG). The statistical analysis was done using Kruskal Wallis, Mann Whitney U tests, and Spearman correlation test. The results showed that there were significant differences in parasitemia (p=0.001), weight (p=0.001), and lung length (p=0.021) between the MA-ARDS and non-MA-ARDS groups. Comparison of NEG and MA-ARDS resulted in a significant difference in lung size (p=0.05). When non-MA-ARDScompared with NEG groups, it showed a significant difference in lung width (p=0.001). However, there was no significant difference in lung weight and length (p>0.05). Spearman correlation test showed that there was a strong correlation between parasitemia with weight (p=0.000), length (p=0.001), and lung width (p=0.017). The findings indicated that parasitemia played a role in the development of MA-ARDS in mice infected with P. berghei ANKA and influenced the size of the lung.